KOMPETENSI GURU DALAM PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM di SMP 3 Limbangan Garut - Asep, Asep Ganjar Sukarelawan; Syamsul Anwar (Khidmatussifa: Journal of Islamic Studies, 2024)
The focus of this study is the development of teacher competency in Multimedia-based learning media to improve Islamic Religious Education learning outcomes at SMP Negeri 3 Limbangan, Garut Regency. The results of the study indicate that the planning of teacher competency development through Multimedia-based learning is as follows: teachers carry out Islamic Religious Education learning planning based on information technology, teachers organize Islamic Religious Education learning, namely organizing learning resources, and teachers realize the Islamic Religious Education learning design that has been prepared, in the syllabus and RPP. The implementation of teacher competency development in Multimedia-based learning is that teachers utilize Power Point Presentations in delivering Islamic Religious Education material to students, teachers use learning videos related to Islamic Religious Education learning materials, and teachers utilize the use of Islamic Religious Education Teaching Media CDs. Evaluation is carried out by evaluating the process carried out on student participation both individually and in groups during the Islamic Religious Education learning process and evaluating the results where Islamic Religious Education teachers evaluate changes in student understanding. Supporting factors for teacher competency through Multimedia-based learning media to improve the quality of Islamic Religious Education learning are increasing student creativity and learning independence, learning materials are more systematic and structured, learning is clear and interesting, easy to use, improve and disseminate; and increasing the role and creativity of Islamic Religious Education teachers. Meanwhile, inhibiting factors include students being more enthusiastic about the internet itself than the material being studied and the learning process being too individualistic, thus reducing social learning.